Сверхсильные магнитные поля - Карцев Владимир Петрович (Новое в жизни, науке, технике, 1967)
Экземпляры: КХ (20181212) / Инвентарный номер: 0170857 / Сис.шифр: 537 / Авт.знак: К 27 / ГРНТИ: 29 / ББК: 22